2017
DOI: 10.1007/s00256-017-2662-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal osteoid osteoma: efficacy and safety of radiofrequency ablation

Abstract: CT-guided RFA is an excellent treatment for spinal OO. Our data suggest that this procedure should be considered for the first stage of therapy for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…Furthermore, the risk of thermal damage to cartilage needs to be considered. Nevertheless, some patients have recurrences after radiofrequency ablation [ 12 ]. Similar risks exist for cryoablation and laser thermocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of thermal damage to cartilage needs to be considered. Nevertheless, some patients have recurrences after radiofrequency ablation [ 12 ]. Similar risks exist for cryoablation and laser thermocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Data reported in the literature have demonstrated that in case of symptomatic recurrence after the first RFA treatment, re-ablation is almost always resolutive with complete disappearance of symptoms, as suggested by the revision of the literature proposed [ 10 , 16 20 , 23 25 , 36 , 39 , 42 44 , 46 , 48 50 28 – 43 , 92 , 44 51 , 54 56 ] (Table 2 ).…”
Section: Radiofrequency Ablation (Rfa)mentioning
confidence: 92%
“…Majority occurred in the lumbar spine which occurred in 59%, in spine frequently located in lamina, pedicles, or the transverse and spinous process [2]. Osteoid osteoma mostly occurred in 5-25 years old and the dominance in male population with a ratio 3:1 to female [3].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging with CT scan may reveal a focal dense lesion with sclerotic reactive bone, and calci cation may appeared. On MRI it may not be as speci c as CT, in which hyperemia and bone marrow edema may discourage the tumoral diagnosis 3 . On Histopathology, macroscopically may be appeared as nidus in distinct round or oval reddish area, and nidus may be soft and granular or may be hard and sclerotic.…”
Section: Introductionmentioning
confidence: 99%